Revitalisasi Tari Radat Selimut Putih: menjembatani Pendidikan Karakter dan pemahaman Budaya Lokal melalui manajemen Seni Pertunjukan - Aditya, Mega Cantik Putri (Academy of Education Journal, 2024)
This research aims to explore the impact of the revitalization of traditional performing arts, especially the Radat Selimut Putih Dance, in an educational context. The performing arts revitalization process not only plays a role in preserving cultural heritage, but also has significant implications in developing character education and understanding of local culture among students. Using a qualitative approach and descriptive methods, this research involved interviews with performing arts revitalization activists and analysis of the performance management process resulting from the revitalization of the Radat Selimut Putih Dance in Serumpun Village. The research results show that the revitalization of traditional performing arts can be an effective means of character education. Through performing arts practice, students can develop values ​​such as cooperation, discipline, perseverance, and a sense of responsibility. In addition, revitalizing the performing arts also provides opportunities for students to understand and maintain their local culture, which can be integrated into the curriculum to enrich students' learning experiences. Thus, this research highlights the importance of integrating traditional performing arts into educational curricula as a significant step in enriching students' learning experiences and strengthening their connection with local culture. It is hoped that the results of this research can contribute to the development of character education and cultural understanding in the educational environment.